Distributing Streaming Media Content using Cooperative Networking - Padmanabhan, Venkat; Wang, Helen; Chou, Philip A.; Sripanidkulchai, Kunwadee (2002)
In this paper, we discuss the problem of distributing streaming media content, both live and on-demand, to a large number of hosts in a scalable way. Our work is set in the context of the traditional client-server framework. Speciﬁcally, we consider the problem that arises when the server is overwhelmed by the volume of requests from its clients. As a solution, we propose Cooperative Networking (CoopNet), where clients cooperate to distribute content, thereby alleviating the load on the server. We discuss the proposed solution in some detail, pointing out the interesting research issues that arise, and present a preliminary evaluation using traces gathered at a busy news site during the ﬂash crowd that occurred on September 11, 2001.